Exploring racial identities through participatory visual and ethnographic methods: (Re)presenting the identities of ethnic minority youth in Hong Kong. Issue 3 (3rd July 2018) - Burkholder, Casey; Gube, Jan
Abstract : There is increasing research attention to the integration of ethnic minority youth in Hong Kong. Within this attention lies an interest in how these young people make sense of their identities in relation to their schooling experiences. From a qualitative methodological viewpoint, researchers' positionalities, including their cultural background and scholarly motivations, have implications on the ways in which they (re)present their findings. Using the axes of insider and outsider, we reflect on and compare how we have approached two studies with ethnic minority youth in Hong Kong. We discuss the potential affordances and tensions of cultural insider and outsider roles in our research to highlight the cultural dynamics in our interactions with our participants. As we advance dialogue on how researchers approach their work through their own cultural positionalities, we offer a nuanced account of the complexities surrounding the 'making' of ethnic minority young people's identities in Hong Kong.